MINDFUL, JOYFUL, DAN MEANINGFUL MELALUI BUKU CERITA ANAK - Shirly Rizki Kusumaningrum; Radeni Sukma Indra Dewi; Mardhatillah; Aprilia Dista Lutvitasari (Al-Mudarris: Journal Of Education, 2025)
This program was conducted to improve the competencies of elementary school teachers at the Laboratory School of Universitas Negeri Malang through the use of children’s storybooks as cross-subject learning media. A total of 25 teachers, teaching Javanese, Physical Education, English, Indonesian, Mathematics, and Science, participated in an in–on–in training model, consisting of face-to-face sessions, online mentoring, and classroom practice. The training materials included the introduction of children’s storybooks, strategies for integrating them into classroom activities, and practical exercises in designing innovative lesson plans. The results of the program revealed a high level of teacher enthusiasm in developing interactive learning by using children’s storybooks, both as a literacy resource and as contextual media across subject areas. Teachers were also trained to follow a systematic process: analyzing learning objectives, selecting appropriate storybooks, preparing pre-reading, while-reading, and post-reading activities, determining relevant assessments, and designing worksheets. This program had a positive impact on enhancing teachers’ competencies in designing mindful, joyful, and meaningful learning that is relevant to students’ needs.